2019
DOI: 10.3389/fchem.2019.00639
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement of Photocatalysis H2 Evolution Over g-C3N4 With Na and Cyano-Group Co-modification

Abstract: Na and cyano-group co-modified g-C3N4 was easily synthesized and its physicochemical property was completely analyzed. The results manifested that Na and cyano-group modification could heighten visible light absorbed ability and accelerate photoinduced charge separation. When resultant Na and cyano-group co-modified g-C3N4 was splitting water H2 evolution, its H2 evolution rate was obviously improved. Furthermore, it also kept excellent stable capacity of H2 evolution and stability of chemical structure. Hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 33 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Figure 10 exhibits the ESR characterization of bCN and mTHPC/pCN under NIR light (λ > 780 nm) at room temperature. bCN and mTHPC/pCN both exhibit one single Lorentz line (g = 2.0034) from 3,200 to 3,800 G magnetic field (Liu G. et al, 2019;Jia et al, 2020). However, compared with bCN, the ESR intensity of mTHPC/pCN is much stronger, indicating that the concentration of unpaired electrons is much higher.…”
Section: Photocatalytic Hydrogen Evolutionmentioning
confidence: 95%
“…Figure 10 exhibits the ESR characterization of bCN and mTHPC/pCN under NIR light (λ > 780 nm) at room temperature. bCN and mTHPC/pCN both exhibit one single Lorentz line (g = 2.0034) from 3,200 to 3,800 G magnetic field (Liu G. et al, 2019;Jia et al, 2020). However, compared with bCN, the ESR intensity of mTHPC/pCN is much stronger, indicating that the concentration of unpaired electrons is much higher.…”
Section: Photocatalytic Hydrogen Evolutionmentioning
confidence: 95%
“…with alkali halide, [11][12][13][14][15][16][17][18][19][20][21][22] a mixture of the prepared GCN and alkali halide, [23][24][25][26][27] a mixture of carbon nitride precursors and alkali metal hydroxide, [28][29][30][31] and a mixture of the prepared GCN and alkali metal hydroxide. 6,[32][33][34][35] Most of the studies revealed that for one or several factors, alkali metal ion doping in GCN can help increase its surface specic area, 6,11,19,20,23,29 promote its crystallinity, 15,17,22,27 enhance its light absorption, 13,[15][16][17]19,21,22,27 reduce its bandgap, 6,13 shi its conduction/valence band, 12,17,…”
Section: Introductionmentioning
confidence: 99%
“…To date, many efforts like adsorption, coagulation, chemical oxidation, deposition, membrane separation, biological, physicochemical, and electrochemical techniques have been utilized to remove these dyes and antibiotics, with a particular focus on MB and TCH (Zhang et al, 2018;Gholami et al, 2019Gholami et al, , 2020Huo et al, 2019b;Kohtani et al, 2019;Li et al, 2019c;Liu et al, 2019b;Wang et al, 2019a). However, long handling times, secondary pollutants and low efficiencies limits the usage of these techniques (Wang et al, 2014;Li et al, 2017Li et al, , 2018Karimi et al, 2019;Liu et al, 2019a;Qi et al, 2019b,c;Shen et al, 2019;Takeda et al, 2019).…”
Section: Introductionmentioning
confidence: 99%